The issue of (self) identification of traditional communities in theses and dissertations of Environmental Education in Brazil - Jimenez Sanchez, Laura del Pilar [UNESP]; Feiteiro Cavalari, Rosa Maria [UNESP] (Federal Univ Rio Grande, Inst Education, 2021)
The present article has the objective of analyzing Brazilian thesis of masters and doctorate in Environmental Education with traditional communities / populations, identifying the denominations used to refer to the social groups that are the focus of production, and the respect for the self-identification. A selection of the masters and doctoral theses found in the Earte Brasil and Capes and BDTD thesis bank was made. The qualitative investigation, type state of the art analyzed twenty-nine documents, but only seven made reference to the self-identification process of the communities. The designation chosen by people external to the community could determine that social groups are seen as passive. These representations are usual in the context of the Social Sciences inherited from Western colonialism that doesn't recognize their role in the processes of global domination. It is necessary to build horizontal dialogues in investigations to give visibility to the reality of communities, as part of the struggle for socioenvironmental justice.
Keywords: Environmental education research; Traditional communities; State of art